2015
DOI: 10.1002/ajmg.a.37495
|View full text |Cite
|
Sign up to set email alerts
|

Survival of children with trisomy 13 and trisomy 18: A multi‐state population‐based study

Abstract: Trisomy 13 (T13) and trisomy 18 (T18) are among the most prevalent autosomal trisomies. Both are associated with a very high risk of mortality. Numerous instances, however, of long-term survival of children with T13 or T18 have prompted some clinicians to pursue aggressive treatment instead of the traditional approach of palliative care. The purpose of this study is to assess current mortality data for these conditions. This multi-state, population-based study examined data obtained from birth defect surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
173
5
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(190 citation statements)
references
References 33 publications
10
173
5
2
Order By: Relevance
“…However, it is important to appreciate that procedural mortality remains high, even in patients with T13 and 18 who were considered to be acceptable candidates for intervention. Defining the ideal timing for surgical intervention, when offered, is not simple because comorbidities that are independent risk factors for mortality, such as prematurity and low birth weight, can affect this decision [6,19,20]. The 15-year survival was significantly higher for patients who underwent a corrective procedure compared to those who underwent palliative procedures only, but this may reflect more complex forms of underlying cardiac disease or more compromised pre-operative clinical status.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is important to appreciate that procedural mortality remains high, even in patients with T13 and 18 who were considered to be acceptable candidates for intervention. Defining the ideal timing for surgical intervention, when offered, is not simple because comorbidities that are independent risk factors for mortality, such as prematurity and low birth weight, can affect this decision [6,19,20]. The 15-year survival was significantly higher for patients who underwent a corrective procedure compared to those who underwent palliative procedures only, but this may reflect more complex forms of underlying cardiac disease or more compromised pre-operative clinical status.…”
Section: Commentmentioning
confidence: 99%
“…The influence of mosaicism or partial trisomy on outcomes is important, and our results demonstrated a significant difference in survival between patients with and without reported mosaicism. Previous studies have reported that mosaic or partial forms of T13/T18 may have improved survival compared to those with full forms of trisomy [6,19]. …”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Birth Defects Prevention Network (NBDPN, ) pooled de‐identified multi‐state population‐based surveillance data for major birth defects, including prevalence and survival by sociodemographic factors (Canfield et al, ; Wang et al, ; Meyer et al, ). We used these data to examine trends in prevalence over time for 26 selected major birth defects, including anomalies of the central nervous, cardiovascular, gastrointestinal, and musculoskeletal systems, oral clefts, and chromosomal anomalies in the United States, from 1999 to 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The NBDPN also publishes pooled data from participating programs; in the 2012 annual report critical CHD surveillance data were highlighted, and the public health role in newborn screening for critical CHDs was discussed . There is also a data repository with data submitted by several states for infants with birth defects born 1999‐2007, which has been used to study the association of race/ethnicity with birth defects, the survival of infants born with birth defects, and may be used to study other issues related to CHDs.…”
Section: Database Categories and Examplesmentioning
confidence: 99%